Edible Coating Base on Aloe Gel with Additives on Strawberry Fruit - Luh Suriati; Ni Made Ayu Suardani S. (SEAS (Sustainable Environment Agricultural Science), 2020)
The edible coating is biodegradable and sustainable packaging has come into attention since the past few decades as an effort to reduce packaging waste. On a landmark fruit, the edible application layer is used to reduce the occurrence of loss of moisture, improve appearance, acts as a barrier to the exchange of gases, as well as having functions as an antifungal and antimicrobial. In addition to extending shelf life can be eaten these many layers are used such as it does not endanger human health, can be eaten as well as easy to untangle nature. One of the natural ingredients that can be used such as a layer of edible is Aloe Vera. From the results obtained that the weight without warming treatment gel stored at cool temperatures is relatively constant, while to gel without or with the treatment of warming that is stored at room temperature a little decline. The reduction drastic invisible on the gel with the saved warming treatment in cold temperatures. Aloe gel good shaped pieces that are stored at room temperature has decreased the weight but that is stored on the cold temperatures are relatively stable. The aloe vera gel with warming and stored at cool temperatures until day 5 relatively stable, as seen from the variable weight shrinkage, color, pH, viscosity, and moisture content. While the gel is stored at room temperature decrease began day 2. Aloe Vera gel should be stored at cool temperatures with a sealed container. The best characteristics of Aloe Vera gel that treatment with sorbitol can extend the shelf life strawberry fruit. edible coating base on Aloe gel can be applied at post-harvest handling fruits.